2014
DOI: 10.1111/jdi.12204
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of carotid and lower limb atherosclerotic lesions in both previously known and newly diagnosed type 2 diabetes mellitus

Abstract: Aims/IntroductionTo compare carotid and lower limb atherosclerotic lesions, and examine if carotid atherosclerotic lesions are in line with lower limb atherosclerotic lesions, and can reflect generalized atherosclerosis in inpatients with type 2 diabetes.Materials and MethodsThis was an observational study carried out in 867 Chinese inpatients with type 2 diabetes, including 573 previously known and 294 newly diagnosed patients. Ultrasonographic assessments of intima-media thickness (IMT), plaques, and stenosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 33 publications
3
23
0
Order By: Relevance
“…In the present study, atherosclerotic plaque and stenosis were defined as the presence of either carotid or lower limb arterial atherosclerotic plaques and stenoses, respectively. The reproducibility of the measurements of carotid and lower limb atherosclerotic lesions had also been reported in our previous studies [ 12 , 14 ].…”
Section: Methodssupporting
confidence: 80%
See 1 more Smart Citation
“…In the present study, atherosclerotic plaque and stenosis were defined as the presence of either carotid or lower limb arterial atherosclerotic plaques and stenoses, respectively. The reproducibility of the measurements of carotid and lower limb atherosclerotic lesions had also been reported in our previous studies [ 12 , 14 ].…”
Section: Methodssupporting
confidence: 80%
“…Both the carotid and lower limb arteries were subjected to Doppler ultrasound examinations that include measurements of IMT, atherosclerotic plaque and stenosis as described in previous studies in detail [ 11 15 ]. The definitions of CIMT, FIMT, carotid and lower limb atherosclerotic plaques and stenosis had also been described in detail in our previous studies [ 11 14 , 16 ]. In the present study, atherosclerotic plaque and stenosis were defined as the presence of either carotid or lower limb arterial atherosclerotic plaques and stenoses, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Carotid IMT (cIMT) and femoral IMT (fIMT) ultrasound measurements have also been studied in CKD patients but with controversial results. While most prior studies have demonstrated increased cIMT in patients with end-stage renal disease [8, 9], others have found no difference in cIMT measurements between CKD patients and healthy individuals [10-12]. We postulated that the controversial results could be due to variability in the grade of atherosclerosis among CKD patients, which could ultimately affect the IMT [13].…”
Section: Introductionmentioning
confidence: 99%
“…Besides coronary arteries, carotid and lower extremity arteries are two other sites where atherosclerotic lesions commonly occur . The multiple correlations and combined diagnosis among coronary, carotid, and lower extremity arteries disease were widely studied and discussed . Previous studies showed that carotid atherosclerotic lesions were an indicator of generalized atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…3 The multiple correlations and combined diagnosis among coronary, carotid, and lower extremity arteries disease were widely studied and discussed. [4][5][6][7][8] Previous studies showed that carotid atherosclerotic lesions were an indicator of generalized atherosclerosis. The carotid atherosclerosis detected by ultrasonography was reported to be a potential marker of atherosclerotic disease and independently associated with cardiovascular and cerebrovascular events.…”
Section: Introductionmentioning
confidence: 99%